Effects of biochar amendment in reducing arsenic and cadmium uptake by sweet corn (Zea mays L.) - Abu Sari, Norazlina (2014)
The use of biochar, a carbon rich product, as a soil amendment has been suggested as a good option for climate mitigation and carbon sequestration. Many types of living biomasses have been used as biochar feedstocks. Empty fruit bunches (EFB) and rice husks (RH) are wastes produced in large quantities from the palm oil and rice industry in Malaysia. These biomasses can be managed appropriately by utilizing them as biochar feedstocks. Some studies have demonstrated the potential of EFB and RH biochars in improving soil properties and crop productivity, but only limited information is available on the effect of these biochars on trace elements uptake by plant. Therefore, the study was conducted with the objective to evaluate the effects of EFB and RH biochars amendment in reducing arsenic (As) and cadmium (Cd) uptake by sweet com (Zea mays L.). There were three experiments were conducted to fulfill the objective which were; characterization, incubation and glasshouse studies. In characterization study, EFB and RH biochars were characterized based on physico-chemical properties to evaluate their potential as sorbent. Both biochars have porous structure with macropores range. The BET surface area of EFB and RH biochars were found as 47 m2/g and 23 m2/g, respectively. The FTIR spectrum obtained in this study suggested that EFB biochar exhibited aromatic compounds meanwhile RH biochar is dominated with aluminosilicate. These compositional differences have an influenced on the carbon (C) content and cation exchange capacity (CEC), whereby the carbon content of EFB biochar was about eight times higher than RH biochar. Based on the characterization, both biochars possesses sorbent properties and this can be confirmed by the adsorption study of As and Cd. In incubation study, three treatments consist of non-amended soil, 20 t C/ha of RH biochar and 2.5 t C/ha of EFB biochar were incubated in the laboratory for 8 weeks. The soil used for the study was naturally contaminated with As and Cd. The soil solution was collected using rhizon moisture sampler on weekly basis. At the end of the incubation period, biochar amended treatments showed significantly lower watersoluble and extractable As than non-amended soil by 74% and 28%, respectively. The alkaline pHs of both biochars which ranged from 9 to 10, had increased the soil pH and might reduce As availability in soil solution. Throughout the incubation period with pH ranging from 3.5 to 5.20, As(V) is expected to predominate in the solution under oxidation condition. Significant higher water-soluble P and K were found in the soil amended with RH and EFB biochars, respectively, than the non amended soil. The effect of biochars on As and Cd was then evaluated further through sweet com uptake in the glasshouse. There were five rates ranging from 0 to 20 t Clha of EFB and RH biochars applied into the contaminated soil. The results indicate that the As uptake by sweet com was reduced significantly with the highest application rate (20 t C/ba) of EFB and RH biochars by 77 and 71%, respectively. Cadmium uptake in contrast showed no significant effect with the addition of biochars compared to the non-amended soil. The low concentration of Cd present in the soil might not be reliable for the evaluation. The soil pH was significantly increased with the addition of EFB and RH biochars. The increased of soil pH was found to be negatively correlated with the increase of extractable As in soil. The changes in soil pH might has influenced As mobility in the soil. Empty fruit bunch and rice husk biochars contain nutrient composition with the following ranges: N- 0.23 to l.63%, P-0.21 to 0.36%, K-O.72 to 5.32%, Ca-0.02 to 0.11 and Mg-0.08 to 0.13%. The high K content in both biochars than other nutrients composition increased significantly the K content of the soil and plant uptake than the control treatment. Plant dry biomass of sweet com increased up to 71% with the addition of biochars compared to the control treatment. The nutrient composition in biochar, especially potassium, act as direct nutrient supplement in soil and enhance the plant growth. The results from this study indicated the potential of EFB and RH biochars in immobilizing As and improving the plant growth with the optimum application rate of 4.2 t Clha (7.5 t biochar/ha) EFB biochar and 4.0 t Clha (50 t biochar/ha) RH biochar. From the research findings, it can be concluded that the application of EFB and RH biochars as soil amendment can reduce the As availability by plants grown in As-rich soils, specifically, in histosol soil of Tangkak, Johor,